Correction to: Contraception and abortion knowledge, attitudes and practices among adolescents from low and middle-income countries: a systematic review - Margarate Nzala Munakampe; Joseph Mumba Zulu; Charles Michelo (BMC, 2019)
In the original publication of this article [1], there are several errors. The original sentences and corrections are listed below: